Melanocytes from Patients Affected by Ullrich Congenital Muscular Dystrophy and Bethlem Myopathy have Dysfunctional Mitochondria That Can be Rescued with Cyclophilin Inhibitors - Zulian, Alessandra; Tagliavini, Francesca; Rizzo, Erika; Pellegrini, Camilla; Sardone, Francesca; Zini, Nicoletta; Maraldi, Nadir Mario; Santi, Spartaco; Faldini, Cesare; Merlini, Luciano; Petronilli, Valeria; Bernardi, Paolo; et al. (Frontiers in Aging Neuroscience, 2014)
Ullrich congenital muscular dystrophy and Bethlem myopathy are caused by mutations in collagen VI genes, which encode an extracellular matrix protein; yet mitochondria play a major role in disease pathogenesis through a short circuit caused by inappropriate opening of the permeability transition pore, a high conductance channel which causes a shortage in ATP production. We find that melanocytes do not produce collagen VI yet they bind it at the cell surface, suggesting that this protein may play a trophic role and that its absence may cause lesions similar to those seen in skeletal muscle. We show that mitochondria in melanocytes of Ullrich congenital muscular dystrophy and Bethlem myooathy patients display increased size, reduced matrix density and disrupted cristae, findings that suggest a functional impairment. In keeping with this hypothesis, mitochondria (i) underwent anomalous depolarization after inhibition of the F-ATP synthase with oligomycin, and (ii) displayed decreased respiratory reserve capacity. The non-immunosuppressive cyclophilin inhibitor NIM811 prevented mitochondrial depolarization in response to oligomycin in melanocytes from both Ullrich congenital muscular dystrophy and Bethlem myopathy patients, and partially restored the respiratory reserve of melanocytes from one Bethlem myopathy patient. These results match our recent findings on melanocytes from patients affected by Duchenne muscular dystrophy (Pellegrini et al., 2013 Melanocytes--a novel tool to study mitochondrial dysfunction in Duchenne muscular dystrophy. J Cell Physiol 228, 1323-1331), and suggest that skin biopsies may represent a minimally invasive tool to investigate mitochondrial dysfunction and to evaluate drug efficacy in collagen VI-related myopathies and possibly in other muscle wasting conditions like aging sarcopenia.